SYNERGY OF OZONE TECHNOLOGY AND UV RAYS IN THE DRINKING WATER SUPPLY AS A BREAKTHROUGH IN PREVENTION OF DIARRHEA DISEASES IN INDONESIA - Ria Wulansarie; S. Bismo (Waste Technology, 2015)
Escherichia coli bacteria which lead to contamination of drinking water in Indonesia, disinfected using ozone technology and UV rays in this research, particularly for solving the problem of water supply. The research was carried out by the variation of samples (tap water and AMDK) and presence or absence of UV rays on the research. All the results, which are related to the number of colonies of E. coli analyzed by using the method of TPC (Total Plate Count). Based on the results of the research, the number of bacteria after disinfection show a significant decline either using ozone alone, UV rays alone, or both, particularly at the time of disinfection for 3 minutes. The most optimal technology for the disinfection process is a synergy between ozone technology and UV rays, proven by the number of bacteria equal to 0 after the disinfection process for 30 minutes.